2010
DOI: 10.1177/1359105310365577
|View full text |Cite
|
Sign up to set email alerts
|

Gardening Promotes Neuroendocrine and Affective Restoration from Stress

Abstract: Stress-relieving effects of gardening were hypothesized and tested in a field experiment. Thirty allotment gardeners performed a stressful Stroop task and were then randomly assigned to 30 minutes of outdoor gardening or indoor reading on their own allotment plot. Salivary cortisol levels and self-reported mood were repeatedly measured. Gardening and reading each led to decreases in cortisol during the recovery period, but decreases were significantly stronger in the gardening group. Positive mood was fully re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
240
2
20

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(303 citation statements)
references
References 34 publications
13
240
2
20
Order By: Relevance
“…However, qualitative studies of children, and a handful of studies in adults, (Armstrong, 2000;Pitt, 2014;Van Den Berg & Custers, 2011;Wakefield et al, 2007) have suggested such a relationship could exist. For example, in a qualitative case study Chawla et al (Chawla et al, 2014) conducted interviews with 52 American adolescents involved in three different gardening programmes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, qualitative studies of children, and a handful of studies in adults, (Armstrong, 2000;Pitt, 2014;Van Den Berg & Custers, 2011;Wakefield et al, 2007) have suggested such a relationship could exist. For example, in a qualitative case study Chawla et al (Chawla et al, 2014) conducted interviews with 52 American adolescents involved in three different gardening programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Gardening is an appealing activity particularly in programs for children and adolescents, as it is hands-on and interactive in nature. Moreover, gardening has been at the core of interventions to improve multiple aspects of health, including nutrition (Bukhari, Fredericks, & Wylie-Rosett, 2011;Davis, Ventura, Cook, Gyllenhammer, & Gatto, 2011;Evans et al, 2012;Heim, Stang, & Ireland, 2009;Lautenschlager & Smith, 2007;McAleese & Rankin, 2007;Morgan et al, 2010;Poston, Shoemaker, & Dzewaltowski, 2005;Ratcliffe, Merrigan, Rogers, & Goldberg, 2011;Robinson-O'Brien, Story, & Heim, 2009;Wang et al, 2010;Wright & Rowell, 2010), educational outcomes (Blair, 2009;Block et al, 2012), mental health (Chawla, Keena, Pevec, & Stanley, 2014;Pitt, 2014;Van Den Berg & Custers, 2011;Wakefield, Yeudall, Taron, Reynolds, & Skinner, 2007) and physical activity (Hermann et al, 2006;Kien & Chiodo, 2003;van den Berg, van Winsum-Westra, de Vries, & van Dillen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, for the subset of UA composed of home and community gardening, a wide body of observational studies report health benefits, such as increasing food security (Bushamuka et al, 2005;Stroink & Nelson, 2009), fruit and vegetable intake (Alaimo, Packnett, Miles, & Kruger, 2008;Armstrong, 2000;Litt, Soobader, Turbin, Hale, Buchenau, & Marshall, 2011;Twiss, Dickinson, Duma, Kleinman, Paulsen, & Rilveria, 2003), and physical activity (Armstrong, 2000;Draper & Freedman, 2010;Park, Shoemaker, & Haub, 2009), while reducing stress (Hawkins, Thirlaway, Backx, & Clayton, 2011;Van Den Berg & Custers, 2011). Building social capital is another documented community and community health-related benefit of gardening (Alaimo, Reischl, & Allen, 2010;Firth, Maye, & Pearson, 2011;Kingsley & Townsend, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Green spaces can have direct benefits on individuals' health, restoring mental fatigue (Kaplan 1995;Kaplan, 2001) and reducing stress levels (Ulrich, 1984;Ulrich et al, 1991;Van Den Berg and Custers, 2011;Adevi and Lieberg, 2012), and indirect ones, stimulating and supporting social interaction and physical activity (Maas et al, 2009), increasing autonomy, improving mood (Rodiek, 2002) and quality of life (Grahn and Stigsdotter, 2003).…”
Section: Introductionmentioning
confidence: 99%